DECONTAMINATION OF MACROALGAE FROM HEAVY METAL POLLUTANT AS RAW MATERIAL FOR ALGAE FLOUR - Tyas Widara, Ratih
Until now, human activities and industry have leaded to several waters in Indonesia, especially those that can disrupt ecosystems and organisms in the environment. The ability to adsorb heavy metals by macroalgae in polluted waters can contaminate these algae. In fact, macroalgae can be used as food with high dietary fiber content. Therefore, in this research, the desorption process of heavy metals from macroalgae was carried out so that it could be used as raw material for algae flour. The aim of this study is to decontaminate macroalgae (Eucheuma sp., Gracilaria sp., Sargassum sp., and Ulva sp.) from heavy metal pollutants so that the algae flour is safe and meets SNI standards.